Temsirolimus inhibits cell growth in combination with inhibitors of the B-cell receptor pathway. Issue 12 (2nd December 2015) - Zoellner, Anna-Katharina; Bayerl, Stephan; Hutter, Grit; Zimmermann, Yvonne; Hiddemann, Wolfgang; Dreyling, Martin
Abstract : Lately, mTOR inhibitors have gained clinical relevance in malignant lymphoma. Still, rapamycin derivatives may activate a pro-survival feedback loop through PI3K-Akt. In this current study, temsirolimus effectively reduced cell growth in GCB and ABC diffuse large cell B-cell lymphoma (GCB = 30–66%, ABC = 45–57%). Combination treatment with the PI3K-δ inhibitor idelalisib additively effected ABC and GCB lymphoma (GCB = 16–38%, ABC = 25–50%). Since Bruton's Tyrosine Kinase (BTK) plays a significant role for the survival of ABC lymphoma, this study also combined the BTK inhibitor ibrutinib with temsirolimus, which resulted in additive cell growth reduction (ibrutinib 50%, temsirolimus 44%, combination 25%) in ABC lymphoma. In contrast, bortezomib, which has been shown previously to be efficient in ABC lymphoma, revealed an antagonistic effect with temsirolimus in some GCB lymphoma (temsirolimus 53%, temsirolimus + bortezomib 63%). Western blot analysis identified the increase of phosphorylated pro-survival kinases Akt and PDK as a possible underlying mechanism of this interaction.